Monitoring sustainable food commons - Loayza, Gabriela; Dangles, Olivier (Frontiers in Sustainable Food Systems, 2025)
The global food system is in the midst of a structural crisis characterized by the commodification of food and the dominance of market-oriented production logic, threatening ecological sustainability and social equity. In response, we propose viewing food systems as socio-ecological commons, the collective management and adaptive governance of which are essential. However, situated monitoring mechanisms that allow for a rigorous and inclusive assessment of their evolution, impacts, and interactions are still lacking. Collaborative monitoring is emerging as a response that is understood not only as a technical monitoring tool, but also as a principle of care, learning, and community co-responsibility. We illustrate our approach through a project that aims to establish pesticide-free food commons in the Ecuadorian Andes. We use the concept of the chakrakamak, a Kichwa term meaning field caretaker, to refer to a person dedicated to monitoring the commons. We generate hybrid indicators that align with the Sustainable Development Goals (SDGs) and the Buen Vivir Goals (BVGs), recognizing the interconnectedness of society, nature, and individual well-being. This approach broadens the theory of the commons, establishes replicable metrics, and strengthens food governance to create more inclusive, equitable, and resilient systems.